Analysis of the Effect of Balance Funds on Economic Growth in Regency/Municipality in Jambi Province - Nurkodri, Moh Sahroni; Malau, Aditya Rahmadillah; Amalia, Fitri (Jurnal Prajaiswara, 2023)
Introduction/Main Objectives: The purpose of this research is to examine the impact of balance funds on economic growth in Jambi Province regencies and municipalities. Background Problems: The greater the ability of the region to meet the costs of regional needs depends on the amount of income generated by the region so that it will be able to meet the needs of the community. Regional economic growth can be made possible through the allocation of balance funds that are managed properly and appropriately, which will later have an impact on regional economic growth. Research Methods: Time series data from 2010 to 2021 were used, as well as cross-section data from 11 regencies and municipalities in Jambi Province. Panel regression analysis was used to examine the data. Finding/Results: The results of the analysis show that, partially and simultaneously, each balance fund has a significant effect on economic growth in the districts and cities in Jambi Province. Conclusion: Based on the results of the analysis, it was found that the allocation of balancing funds plays an important role in economic growth in the regions. Balancing funds must be managed effectively and efficiently so as to increase economic growth in the region and improve people's welfare.